Analisis Standar Operasional Prosedur (SOP) pada Petugas Perawatan Pasien Gangguan Jiwa di Bangsal Zaitun BLUD RSU Cut Nyak Dhien Aceh Barat - Luthfi, Fakhrurradhi; Safrizal, Safrizal; Maulana, Fajar (Jurnal Riset Hesti Medan, 2023)
Standard Operating Procedures (SOP) is a system prepared to make work easier, neater and more orderly. This system contains the sequence of the process of carrying out work from start to finish. The problem in this research is to find out how the SOP actions carried out in the room by officers in the care of mental disorders patients are carried out. Handling non-urgent emergencies, philosophy of the purpose of the inpatient room, and protocol for accepting patients with mental disorders in the Zaitun Ward. This type of research is qualitative, descriptive in nature, the method used is in-depth interviews. The informants in this study were 7 people. The results of the study showed that the handling of emergency and non-emergency patients carried out by Mentally Disordered Patient Care Officers in the Zaitun Ward BLUD RSU Cut Nyak Dhien Meulaboh showed that the officers immediately took action without communicating first with the patient's family so that the patient's family did not understand challenge how the mechanism for handling critical and non-emergent patients should be implemented. The philosophy and objectives of inpatient care show that patient admission is carried out through the emergency room and then taken to a room to be treated in the olive ward. Apart from that, the explanation from the staff regarding patient admission was found to be that the family received an explanation regarding the patient's admission. Olive Ward. The Protocol for Admission of Patients with Mental Disorders shows that the family does not understand the explanation or procedures and mechanisms from officers regarding the complete administration of patient admission at the Olive Ward BLUD RSU Cut Nyak Dhien Meulaboh. Suggestions for officers are expected to work in accordance with existing operational standards in the room for a smooth service process in the hospital, especially in the olive ward.